OX2R activation induces PKC-mediated ERK and CREB phosphorylation - Guo, Yang (2012)
Deficiencies in brain orexins and components of mitogen activated protein kinase (MAPK) signaling pathway have been reported in either human depression or animal model of depression. Brain administration of orexins affects behaviors toward improvement of depressive symptoms. However, the documentation of endogenous linkage between orexin receptor activation and MAPK signaling pathway remains to be insufficient. In this study, we report the effects of orexin 2 receptor (OX2R) activation on cell signaling in CHO cells over-expressing OX2R and in mouse hypothalamus cell line CLU172. Short-term extracellular signal-regulated kinase (ERK) phosphorylation and long-term cyclic adenosine monophosphate (cAMP) response element binding protein (CREB) phosphorylation were subsequently observed in CHO cells that over-express OX2R while 20 min of ERK phosphorylation was significantly detected in mouse adult hypothalamus neuron cell line CLU172. Orexin A, which can also activate OX2R, mediated ERK phosphorylation was as the same as orexin B in CHO cells. A MAPK inhibitor eliminated ERK phosphorylation but not CREB phosphorylation in CHO cells. Also, ERK and CREB phosphorylation was not mediated by protein kinase A (PKA) or calmodulin kinase (CaMK). However, inhibition of protein kinase C (PKC) by GF 109203X eliminated the phosphorylation of ERK and CREB in CHO cells. A significant decrease in ERK and CREB phosphorylation was observed with 1 μM GF 109203X pre-treatment indicating that the conventional and novel isoforms of PKC are responsible for CREB phosphorylation after OX2R activation. In contrast, ERK phosphorylation induced by orexin B in CLU172 cells cannot be inhibited by 1 μM of protein kinase C inhibitor. From above observation we conclude that OX2R activation by orexin B induces ERK and CREB phosphorylation and orexin A played the same role as orexin B. Several isoforms of PKC may be involved in prolonged CREB phosphorylation. Orexin B induced ERK phosphorylation in mouse hypothalamus neuron cells differs from CHO cell line and cannot be inhibited by PKC inhibitor GF 109203X. And hypothalamus neuron cells may use different downsteam pathway for orexin B induced ERK phosphorylation. This result supports findings that orexins might have anti-depressive roles.